Stabilisasi Tanah Lempung yang Dicampur Zat Additive Kapur dan Matos Dtinjau Dari Waktu Perendaman - Herdiana, I Komang Tri; Iswan, Iswan; Zakaria, Ahmad (Universitas Lampung, 2018)
In order to obtain a good, strong and sturdy foundation layer, good soil carrying capacity is required. In addition, the soil also serves to support the foundation of a civil construction such as buildings and pavement. Therefore it is necessary to do soil improvement for soil types that have low carrying capacity. In this final project, a research on high plasticity clay soil is taken from Sidorejo area, Sidomulyo district, South Lampung to find CBR value with variation of immersion time. From this research, we can see the change of CBR value with immersion variations that have been done for 4, 5, 14, and 28 days.From the research conducted in the Laboratory of Soil Mechanics of Lampung University , it is known that the soil originating from Sidorejo area, Sidomulyo District Southern Lampung is classified into A-7-5 clay soil which has a soil bearing capacity value of 7%. After the improvement of soil with lime additive substances with optimum content of 12% and 3,472 gr of matos stabilizer which is then done with immersion test with a duration of 4, 5, 14 and 28 days, the value of CBR is 24% at 4 days, 22% at 5 days, 15.6% at 14 days and 9% at 28 days. The value of CBR obtained tends to decrease as the duration of immersion is increased, so it can be concluded the duration of immersion greatly affects the size of soil bearing capacity.